Formulation Development and Evaluation of Iloperidone Loaded Nanosuspension for Solubility Enhancement - Jadhav, Shivraj Popat; Dhakad, Prashant Kumar; Gupta, Tapasvi; Gilhotra, Ritu (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Iloperidone is categorised as an antipsychotic drug and is used to treat schizophrenia. Iloperidone belongs to the Biopharmaceutics Classification System class II due to its low water solubility. Objectives: The primary aim of this work is to develop a nanosuspension of iloperidone to address issues such as low solubility and insufficient bioavailability. A 32 complete factorial design was employed to explore the influence of stabiliser concentration (A) and probe ultrasonication time (B) at three different levels as independent factors on the size of particles (Y1) and saturation solubility (Y2) as dependent variables. Materials and Methods: Solvent-antisolvent method with probe ultrasonication was used for the formulation of nanosuspension. Optimized nanosuspension was then assessed for several parameters like saturation solubility, particle size, SEM, % of the drug, zeta potential, thermal analysis, FTIR, in vitro and in vivo analysis. Results: The optimized formulation has shown 286.67 nm particle size and 164.33 μg/mL saturation solubility. Zeta potential measurement of optimized formulation has indicated -25.8 mV potential which was enough to keep suspension in nano size. SEM images of lyophilized optimized nanosuspension formulation revealed particle size less than 1 μm. Optimized formulation has shown near about 100% drug release in 20 min. In vivo studies have indicated that the optimized nanosuspension exhibited a 2.88-times increase in Cmax, a 2-fold increase in AUC and less time to reach Tmax. Stability studies indicated acceptable stability over three months. Conclusion: In conclusion, the results of the present investigation indicate that nanosuspension technology can enhance the solubility as well as the bioavailability of iloperidone.
Keywords: Solubility; Nanosuspension; Pharmacokinetic; Schizophrenia; Factorial design